Malignant fungating wounds assessment in palliative care: a scoping review - Nigrelli, Daniela; Gambalunga, Francesca; Anastasi, Giuliano; Peghetti, Angela; Durante, Stefano; Giusti, Martina; Biagioli, Valentina; Quirini, Silvio; Iacorossi, Laura; Latina, Roberto (Frontiers in Public Health, 2025)
IntroductionMalignant fungating wounds (MFWs) are secondary chronic wounds resulting from malignant cell proliferation and migration, compromising skin integrity in patients with cancer. These wounds present a range of signs and symptoms. Although several instruments are used in their assessment, it is still unclear which tool is most appropriate for comprehensive evaluation and wound healing.AimTo review the existing instruments for MFW assessment, highlighting their strengths and limitations.MethodsA scoping review was conducted following the Arksey and O’Malley framework (2005), the Joanna Briggs Institute guidelines (2020, 2021), and the PRISMA-ScR checklist (2018). The search was performed on four databases: Web of Science, Scopus, PubMed, and EBSCO.ResultsForty studies were included, describing 22 instruments. They described half targeted general symptoms, and half wound-related signs and symptoms. Four instruments were specifically designed for MFWs, all based on the Malignant Wound Assessment Tool (MWAT). These were: MWAT – Clinical; MWAT– wound bed status; MWAT– Perception; MWAT – Research. However, only the Clinical and Research versions were validated in English, but neither was subjected to psychometric validation, and lacked a comprehensive assessment, such as key symptoms.ConclusionDespite the existence of specific tools for MFW assessment, a comprehensive, validated, and standardized tool is still lacking. While the Clinical and the Research versions of the MWAT offer a broad assessment of MFWs, they require refinement to address overlooked symptoms and validation in other languages. Establishing standardized, multidimensional measures could enhance clinical decision-making and improve outcomes for patients living with MFWs.